(untitled) (Transport systems and technologies, 2019)
Modern high-speed ground vehicles are implemented on the application of magnetic levitation technology, when the vehicle in the process of movement does not concern the way structure. High speeds and small levitation distances create difficulties in ensuring the reliability and safety of such transport functioning, lead to the impossibility of using traditional control means, which requires the development of control methods based on new physical phenomena. Taking into account the distinctive features of a magnetically-levitative vehicle and the degree of influence of its systems on the catastrophic consequences of failure in general, a way structure was proposed as a generalized object of control, and microwave radiation accompanying destruction as an information signal of the process of destruction of the track structure. A certain relationship has been established between the parameters of electromagnetic emission arising from the cracklings of way structure materials and its strength, which makes it possible to implement a passive non-destructive dynamic control device for the way structure of the high speed transport, for which a high informativeness and high-speed are characteristic and which ensures high reliability and safety of modern high-speed vehicles.